Soft Coulomb gap and asymmetric scaling towards metal-insulator quantum criticality in multilayer MoS2 - Byoung Hee Moon (Nature Portfolio, 2018)
The interplay between strong interactions and presence of disorder makes atomically thin transition metal dichalcogenides an ideal platform to study phase transitions and critical phenomena. Here, the authors observe asymmetric critical exponents around the metal-insulator-transition of multilayer MoS2.